Higiena ustne votline v rehabilitacijski zdravstveni negi otroka - Blaznek, Meta (Rehabilitacija (Ljubljana), 2014)
Introduction The aim of this research was to evaluate the level awareness about importance of oral hygiene and regular cleaning of the oral cavity in a sample of children who were referred to inpatient rehabilitation at the children's department of the Universsity Rehabilitation Institute in Ljubljana, Slovenia. Methods We invited parents of children who were hospitalised in the period from the beginning of January till the end of June 2013. We collected data on how frequently children were cleaning their teeth, if they needed any help and how frequently they were visiting a dentist. We also organised a series of workshops for parents on appropriate oral hygiene for children. Results Most of the hospitalised children needed supervision or help from another person for cleaning of the oral cavity. Oral hygiene of children with severe impairments was very difficult to maintain and they needed help. Most of the children visited their dentist on a regular basis. Conclusion The majority of children hospitalised for inpatient rehabilitation need help to maintain oral hygiene.
Keywords: Child; Health Education; higiena ustne votline; hygiene of the oral cavity; otroci; prevention; preventiva; Rehabilitation Nursing; Tooth; zdravstvena nega; zdravstvena vzgoja; zobje